Fetal ECG Extraction from Multichannel Abdominal ECG Recordings for Health Monitoring During Labor. (2016) - Ionescu, Viorel
Abstract: Extracting clean fetal electrocardiogram (fECG) signals from non-invasive abdominal ECG recordings for monitoring the health of the fetus during pregnancy and labor remains a big challenge. The proposed system for facing extraction, processing and morphological feature estimation was implemented in LabVIEW 2013 with preinstalled Biosignal Filtering, Advanced Signal Processing and Digital Filter Design Toolboxes. The present approach is based on the using of FastICA algorithm for fECG extraction. In order to improve fECG extraction performance, it was applied here a combination of Undecimated Wavelet Transform (UWT) and Fast Fourier Transform (FFT) – Inverse Fast Fourier Transform (IFFT) algorithm as post-processing tool. Fetal ECG morphological indicators like heart rate, T/QRS ratio and QT interval could be estimated from fECG post-processed signals of two patients and some considerations regarding to the fetal stress during labor could be made in these two cases.